Experimental Investigation on Pressure Drop of R22 and R410a during Condensing Process in Microtubes - Zhang Huiyong; Li Junming; Wang Buxuan (Zhileng xuebao, 2007)
R410a is known as one of the substitutes for R22 and it is important to study the pressure drop of R410a during condensing processes. A test rig was established to measure pressure drop in micro scale and characteristics of pressure drop of R22 and R410a in a horizontal stainless round tube with an inner diameter of O. 941 mm during condensing processes were investigated experimentally at the saturation temperature of 40%. The mass flux varied within the range of 200- 1000 kg/m^2 s and the vapor quality 0. 2- 0. 8. The experiment results indicate that pressure drop increases with mass flux and vapor quality and more obviously in high vapor quality region. The pressure drop of R410a is equivalent to that of R22 at low vapor quality and mass flux but obviously lower than that of R22 at higher vapor quality and mass flux.